Importance of the study of the vitreous body for the diagnosis of diabetes mellitus and diabetic ketoacidosis post-mortem. About a case (2016)
Type 1 Diabetes Mellitus usually begins with ketoacidosis, one of its complications that can lead to death quickly. This condition may go unnoticed, requiring medical and legal autopsy. Among the samples of major interest in the autopsy is the vitreous humor, which is used for detection of glucose levels, electrolytes and others. We present the case of a 15-year-old girl with no significant history, who died after presenting with pharyngotonsillitis and the pathological findings did not allow the cause of death to be identified, however, the vitreous humor study revealed elevated glucose levels and Increased blood levels of acetone. We discussed the importance of collecting the vitreous humor for the diagnosis of metabolic diseases. © 2016, Asociacion Andaluza de Medicos Forenses. All rights reserved.